Comparative analysis of the performance of the Indonesian and Malaysian islamic capital markets during the COVID-19 pandemic - Rina ASnita Rina ASnita; Abel Tasman (Universitas Negeri Padang, 2022)
The purpose of the study is to analyze of the Indonesian and Malaysian Islamic capital market during the COVID-19 pandemic using the Sharpe, Treynor and Jensen index models. The type of this research is comparative descriptive. The population in this study are all Indonesian and Malaysian Islamic capital market indexes listed on BEI and BM in 2020. Based on the sampling technique, namely purposive sampling the samples in this study were JII and JII 70 as well as FBMS and FBMHS. The results on this study are the differences in performance between the Indonesian and Malaysian Islamic capital markets measured using the Sharpe and Treynor indexes, While if measured using the Jensen index, the results show that there is no difference in performance between the Indonesian and Malaysian Islamic capital markets in 2020.